Public Effort and Participation in the Enforcement of Corruption Eradication in Indonesia - Mangaraja Manurung; Dany Try Hutama Hutabarat (Universitas Negeri Semarang, 2023)
Corruption remains a pressing issue with far-reaching adverse effects on numerous aspects of human existence globally. Combating corruption is a crucial priority in Indonesia that requires concerted efforts. This study employs a normative legal research methodology to construct and conceptualize laws based on applicable doctrines and legal concepts. In addition, it employs a case study approach to investigate specific instances of corruption in depth. This study aims to provide an overview of the regulations regarding the eradication of corruption and to demonstrate how community involvement can contribute to enforcing anti-corruption measures. The results show that Law Number 1 of 2023 concerning the Criminal Code in the article concerning corruption, the penalties set for corruptors are very far from what they are entitled to receive. In relation to reports of corruption cases, this study suggests that a public education strategy aiming at educating the general public directly or via social media must be conducted. This strategy intends to increase public awareness and encourage membership in the IFC (Indonesia is Free of Corruption) organization, which provides legal protection against alleged corruption offenders. In addition, regarding the punishment for corruptors, DPR RI (House of Representatives) are suggested to revise the current law that perpetrators of corruption who have amassed more than Rp 100,000,000 will face court-determined punishments, such as the return of illicit gains or the maximum penalty of the death penalty.